Iowa Birdline update, February 21, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for February 21, 1994. Highlights include the sighting of a Greater Prairie-Chicken. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed